Introduction to the theory of heavy-ion collisions - Nörenberg, Wolfgang; Weidenmüller, Hans-Arwed (Lecture notes in physics, 1976)
1. Introduction -- 2. Classical theory of HI collisions -- 3. Gross properties of HI reactions. Compound-nucleus formation -- 4. Some elements of nuclear scattering theory -- 5. Elastic scattering -- 6. Coulomb excitation -- 7. Inelastic scattering and transfer reactions -- 8. Statistical theory -- 9. Atomic effects in ion-atom collisions
Keywords: Ionenstoß; Schweres Ion; Schwerionenstoß; Theorie; Schwerionenstreuung